Guinness worl records 2021 Annual edition (Pakistan : Paramount Books (Pvt. ) Ltd. , Guinness World Records Limited, 2021)
Guinness World Records 2021 is a vibrant, fact-packed annual showcasing the most incredible achievements and record-breaking feats from around the world. Featuring stunning photography, fascinating facts, and themed sections on science, adventure, sports, animals, and human extremes, it also includes interactive elements like augmented reality and at-home challenges, making it both an entertaining read and an inspiring reference for all ages.
Keywords: General Works - Reference Book